Niger Urbanization Review : Supporting Niger's Modern Oases - World Bank (World Bank, Washington, DC, 2021)
The Niger Urbanization Review aims to improve our understanding of urbanization and local governance in Niger by analyzing the current and potential contribution of urbanization to the country’s long-term national development and the institutional and financial capacity of local governments to manage the urbanization process. Urgent attention is needed to manage Niger’s rapid urban population growth. This review seeks to inform how urban areas can leverage the concentration of population to deliver services more efficiently and provide the enabling environment required to support the transformation of Niger’s economy, creating more productive off-farm jobs as set out in the best-case scenario of the National Social and Economic Plan 2017- 2021.Urban centers can play a pivotal role in the delivery of essential services for their populations and associated hinterlands and in realizing the potential of their emerging role as foci for economic development. While Niger has embarked on reform efforts towards decentralization and devolution of power to the local level since the 1990s, progress made towards the implementation of these reforms has been limited. The review is divided into five chapters. Chapter first looks at the patterns of urbanization in Niger, and how they contrast with the experience in the rest of the world. Chapter second goes through opportunities and challenges brought on by urbanization, looking at living standards and the structure of the economy across settlement patterns. Chapter third examines rural-urban linkages before discussing different urbanization scenarios for the period 2015-2035. Chapter fourth looks at the existing institutional and fiscal framework and its impact on urban management in general and on capital investments in particular. Lastly, the fifth chapter provides an overview of policy implications and offers operational recommendations for a possible way forward.